EVOLUTION OF JOURNALISM: FUNCTIONAL AND STYLISTIC FEATURES OF BLOGGING - Volodymyr Hnot; Paraskoviya Dvorianyn (Інтегровані комунікації)
In the era of new technologies and information globalization, Internet platforms have become not only platforms for exchanging ideas but also express channels for gaining popularity and influence. One such dynamic form is blogging – a phenomenon that permeates the modern media sphere, transforming its usual framework and rewriting the rules of the game. The relevance of the study is due to the fact that in recent years, blogging has become an important component of the media landscape, both in the Internet space and beyond. The purpose of the study is to identify and analyze the functional and stylistic transformations that have occurred in journalism as a result of the development and spread of blogging as a new form of media communication. By the stated purpose of the study, our task is to analyze changes in the style of journalistic materials under the influence of blogger communication. The study used theoretical methods (analysis of scientific literature, system analysis, content analysis) and empirical methods (qualitative analysis of texts and observations).